UTILIZATION OF LIQUID ORGANIC FERTILIZER TO BREAK SEED DORMANCY AND GROWTH OF SUGAR APPLE (Annona squamosa L.) SAPLINGS - Junita; Wahyu Lestari (BIOMA : Jurnal Ilmiah Biologi, 2025)
Generative propagation of sugar apple has obstacles caused by the hard seed coat that inhibits the imbibition process and the seeds become dormant. Liquid organic fertilizer (LOF) can be used as a solution to break seed dormancy and the growth of sugar apple (Annona squamosa L.) seedlings. This study is conducted to determine the right concentration and soaking time of LOF, as well as to determine the effect of the interaction between concentration and soaking time of LOF for breaking seed dormancy and growth of sugar apple seedlings. The research is conducted using a randomized complete factorial design with 2 factors, namely LOF concentration (0%, 25%, 50%, 75%, 100%) and soaking time (6, 12, 18, 24 hours). Data are analyzed using ANOVA and DMRT further test at 5% level. The results shows that the LOF concentration, soaking time and the interaction between the combination of LOF concentration and soaking time are not yet obtained to break seed dormancy and the growth of sugar apple seedlings. The use of 25% LOF concentration showed significant differences with other LOF concentration treatments (50, 75, 100%) on growth parameters (plant height, number of leaves and fresh biomass), but not significantly different compared to the control on all germination and growth parameters. Soaking times of 6 hours and 12 hours are not significantly different on all germination and growth parameters, but significantly different from soaking 18 hours and 24 hours on germination parameters (germination percentage and vigor index). The interaction of LOF concentration and soaking time is not significantly different on all germination and growth parameters.